Penerapan Metode Eksperimen Berbantuan Lembar Kerja Peserta Didik Untuk Meningkatkan Minat Belajar Fisika Peserta Didik Kelas X SMA - Puri, Putri Rose Amanda; Pujianto, Pujianto (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2025)
Physics learning does not only include products, but also includes processes and attitudes so that it requires experimental methods that can encourage students to carry out scientific activities. Students' interest in learning is one of the obstacles faced in learning physics today so that the purpose of this research is to increase students' interest in learning physics using experimental methods assisted by LKPD. Quantitative method with pseudo experiment type was used in this research. This research was conducted at SMA N 1 Sanden involving 33 students of class XB as the experimental group and 33 students of class XC as the control group. The results of the data analysis of physics learning interest using the Independent Sample T-Test test obtained a significance value of 0.968 which showed that there was no significant difference in the physics learning interest of students who used the experimental learning method assisted by LKPD with students who used the conventional model in the control group. In using the experimental method, teachers must provide preliminary material first, ensure the number of experimental tools is sufficient, and allocate sufficient time so that students' interest in learning can increase